Clinical outcomes in the surgical management of ankle fractures: A systematic review and meta-analysis of fibular intramedullary nail fixation vs. open reduction and internal fixation in randomized controlled trials. Issue 7 (October 2022) - Walsh, John P.; Hsiao, Mark S.; LeCavalier, Daniel; McDermott, Ryland; Gupta, Shivali; Watson, Troy S.
Abstract: Background: What level I evidence exists to support the use of FNF for surgical management of ankle fractures in high risk patients? The purpose of this study was to compare clinical outcomes following fibular intramedullary nail fixation (FNF) and open reduction and internal fixation (ORIF) of ankle fractures. Methods: A systematic review of the current literature was performed according to Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Certainty of evidence reported according to GRADE (Grading of Recommendations Assessment, Development, and Evaluation). Our primary hypothesis was that patients undergoing FNF procedures to manage an ankle fracture would have significantly higher patient reported outcome scores (PROs) than patients undergoing ORIF. Primary study outcome measures were validated PROs. Secondary outcome measures included complication rate, secondary surgery rate, and bony union. Results: The primary outcome analysis revealed no evidence of a significant effect difference on Olerud and Molander Ankle Score (OMAS) PRO and no evidence of statistical heterogeneity. Secondary outcome analysis revealed a significant 0.30 (0.12–0.74 95CI) relative risk reduction for complications in FNF (P = 0.008). No evidence of an effect difference for bony union. The GRADE certainty of the evidence was rated as low for bone union. No evidence of reporting bias was appreciated. Sensitivity analyses did not significantly alter effect estimates. Conclusion: This systematic review and meta-analysis restricted to evidence derived from RCTs revealed that the quality of evidence is reasonably strong and likely sufficient to conclude: (1) there is likely no clinically important difference between FNF and ORIF up to 12 months post-operatively, as defined by OMS (moderate certainty); (2) surgeons may reasonably expect reduced complications in 14 out of every 100 patients treated with FNF (moderate certainty); (3) there is likely no difference in bony union (low certainty). Future studies should investigate more patient-centered outcomes and if short-term findings are durable over time if these findings apply to lower risk populations. Level of Evidence: Systematic review and meta-analysis of level I evidence